2016
DOI: 10.3390/ijms17071052
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality and Cancer Outcomes in Adults: A Systematic Review of Epidemiological Studies

Abstract: Dietary patterns influence cancer risk. However, systematic reviews have not evaluated relationships between a priori defined diet quality scores and adult cancer risk and mortality. The aims of this systematic review are to (1) describe diet quality scores used in cohort or cross-sectional research examining cancer outcomes; and (2) describe associations between diet quality scores and cancer risk and mortality. The protocol was registered in Prospero, and a systematic search using six electronic databases wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 89 publications
0
31
2
1
Order By: Relevance
“…4 All but one of the reports from the eight individual studies investigating the association between a diet quality index and colorectal cancer reported an inverse relationship. 5 Of these seven studies, three used a variation of the Mediterranean diet score, two used adaptations of the DASH index, and two used HEI variants. 5 A pooled analysis of nine cohort studies studying adherence to a Mediterranean diet showed a 9% reduction (95% CI for HR: 0.84–0.98) in colorectal cancer incidence for the highest vs. lowest quantile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 All but one of the reports from the eight individual studies investigating the association between a diet quality index and colorectal cancer reported an inverse relationship. 5 Of these seven studies, three used a variation of the Mediterranean diet score, two used adaptations of the DASH index, and two used HEI variants. 5 A pooled analysis of nine cohort studies studying adherence to a Mediterranean diet showed a 9% reduction (95% CI for HR: 0.84–0.98) in colorectal cancer incidence for the highest vs. lowest quantile.…”
Section: Discussionmentioning
confidence: 99%
“…5 Of these seven studies, three used a variation of the Mediterranean diet score, two used adaptations of the DASH index, and two used HEI variants. 5 A pooled analysis of nine cohort studies studying adherence to a Mediterranean diet showed a 9% reduction (95% CI for HR: 0.84–0.98) in colorectal cancer incidence for the highest vs. lowest quantile. 6 A systematic literature review of five case-control and seven cohort studies also supported the association between a higher overall diet quality, including Mediterranean diet score and HEI, and a lower risk of colorectal cancer, and suggested similar associations for men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Higher fruit and vegetable consumption, as part of a dietary pattern that includes less energy dense foods and higher intakes of fibre and associated micronutrients, has been linked to smaller weight gain over time[2], several types of cancer[3] and lower risk of cardiovascular mortality[4]. The health benefits of regular physical activity are also irrefutable, with risk reductions of at least 20%-30% for more than 25 chronic medical conditions and premature mortality[5].…”
Section: Introductionmentioning
confidence: 99%
“…There exists a strong yet inverse relation between positive lifestyle, healthy dietary patterns, and cancer incidence. Healthy diet reduces the risk of postmenopausal breast cancer, colorectal cancer, and head and neck cancer (Potter et al, 2016). A diet which is mainly plant-based and is low in red and processed meats, simple sugars, and refined carbohydrates can definitely contribute enormously toward cancer prevention (Bail et al, 2016).…”
Section: Diet and Lifestylementioning
confidence: 99%